The wheels on the bus - Kovalski, Maryann (London : Scott Foresman, 1995)
While a grandmother and grandchildren wait for the bus, they sing the title song with such gusto they miss their bus.
2.0
K-3.
K-3
Keywords: Buses -- Songs and music; Songs; Buses -- Songs and music; Songs